Comparative outcomes of cefazolin versus antistaphylococcal penicillins in methicillin-susceptible Staphylococcus aureus infective endocarditis: a post hoc analysis of a prospective multicentre French cohort study. (July 2021) - Lecomte, Raphaël; Bourreau, Alexis; Deschanvres, Colin; Issa, Nahéma; Le Turnier, Paul; Gaborit, Benjamin; Chauveau, Marie; Leroy, Anne-Gaëlle; Le Tourneau, Thierry; Caillon, Jocelyne; Camou, Fabrice; Boutoille, David
Abstract: Objectives: Current guidelines recommend cefazolin as an alternative to antistaphylococcal penicillins (ASPs) in methicillin-susceptible Staphylococcus aureus (MSSA) infective endocarditis despite the lack of comparative study. The objective of this study was to evaluate the comparative outcomes of cefazolin vs. ASPs in MSSA infective endocarditis. Methods: This was a retrospective analysis of an observational multicentre cohort study using prospectively collected data from patients with MSSA endocarditis confirmed by endocarditis team and treated either with cefazolin or ASPs between July 2013 and December 2018. Patients were excluded if they received both treatments. The primary outcome was 90-day all-cause mortality. Results: Of 210 patients included, 53 patients (25.2%) received cefazolin and 157 (74.8%) received ASPs. The overall 90-day mortality rate was 27.6% (58/210 patients), 24.5% (13/53) in the cefazolin group vs. 28.7% (45/157) in the ASP group (p 0.561). Premature antimicrobial discontinuation due to adverse events occurred less frequently with cefazolin than with ASPs (0/53 vs. 13/157 patients; p 0.042). In multivariate analysis, there was no difference in 90-day mortality between cefazolin and ASPs (adjusted odds ratio (aOR), 1.2; 95% confidence interval (CI), 0.49–2.91; p 0.681), while age (aOR, 1.06; 95% CI, 1.03–1.09; p < 0.001), Charlson comorbidity index (aOR, 1.18; 95% CI, 1.02–1.36 p 0.023), cerebral embolism (aOR, 2.83; 95% CI, 1.33–6.14; p 0.007) and intensive care unit admission (aOR, 4.16; 95% CI, 1.89–9.59; p 0.001) were factors significantly associated with higher mortality. Conclusions: Cefazolin seems to be a possible alternative to ASPs in MSSA endocarditis. More studies are needed to confirm these results and determine which treatment should be recommended as first-line therapy.